Berita BERNAMA memelihara khazanah negara - Ibrahim, Hasnita (Persatuan Pustakawan Malaysia, 2005)
Malaysians read newspapers and listen to the news broadcast daily. Various ways are used to report the daily happenings in Malaysia as well as abroad and in most cases the sources of the news is BERNAMA. This article is an attempt to familiarise the public with BERNAMA, a Malaysian-based news agency.